2002
DOI: 10.1046/j.1537-2995.2002.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomated data analysis of flow cytometric estimation of fetomaternal hemorrhage in D− women

Abstract: Semiautomated data acquisition and calibration curve analysis represents a further step toward standardization of flow cytometry for accurate FMH quantification and facilitates evaluation and control of day-to-day variations between laboratories, flow cytometers, and operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The evaluation of the performances of the Fetal Cell Count kit demonstrates a good linearity and precision of the method for artificial mixtures ranging from 0.01 to 5.00 percent fetal cells representative of more than 99.9 percent of the clinical situation with FMH 1 . These data are very close to those obtained by other investigators performing flow cytometry with a single marker 17,38,40,41 . They confirm that flow cytometry is more precise than the KBT known to have a poor reproducibility 4,42 despite several attempts to standardize the method 43 and the introduction of external quality assurance scheme for Kleihauer testing 44 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The evaluation of the performances of the Fetal Cell Count kit demonstrates a good linearity and precision of the method for artificial mixtures ranging from 0.01 to 5.00 percent fetal cells representative of more than 99.9 percent of the clinical situation with FMH 1 . These data are very close to those obtained by other investigators performing flow cytometry with a single marker 17,38,40,41 . They confirm that flow cytometry is more precise than the KBT known to have a poor reproducibility 4,42 despite several attempts to standardize the method 43 and the introduction of external quality assurance scheme for Kleihauer testing 44 .…”
Section: Discussionsupporting
confidence: 75%
“…1 These data are very close to those obtained by other investigators performing flow cytometry with a single marker. 17,38,40,41 They confirm that flow cytometry is more precise than the KBT known to have a poor reproducibility 4,42 despite several attempts to standardize the method 43 and the introduction of external quality assurance scheme for Kleihauer testing. 44 Two major reasons may explain these findings.…”
Section: Discussionmentioning
confidence: 87%
“…After repeating this washing step three times, 50 μL monoclonal FITC‐conjugated anti‐D (LDG76) antibody (Quant‐Rho, Quotient Biodiagnostics, Newtown, PA) was added, and the solution was mixed thoroughly by vortexing. This antibody is an IgG1κ heterohybrid (human‐murine) monoclonal antibody specific for epD3 in the nine epitope model and epD5 in the thirty‐six epitope model of D antigen and has been shown to have a high affinity for D antigen, achieving sufficiently high antibody‐to‐cell ratio [20]. The volume of antibody was determined in pilot experiments to ensure antibody saturation (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Initial FC assays targeted the D antigen on fetal RBCs, distinguishing D+ fetal RBCs from D-maternal RBCs using polyclonal or monoclonal anti-D reagents. 46,[67][68][69][70][71][72][73][74] Nance and colleagues 67 compared the results of testing mixtures of D+ cord RBCs and D-adult RBCs by the rosette screen, K-B acid elution assay, and an FC (anti-D) assay. They reported that results by FC (anti-D) were more accurate, reproducible, and sensitive.…”
Section: Flow Cytometry Anti-d Methodsmentioning
confidence: 99%